Canadian yearbook of international law (Cambridge University Press)
The Canadian Yearbook of International Law has been a leading international academic journal covering both public and private international legal issues. Authors from Canada and around the world are invited to publish peer-reviewed articles in French or English that advance critical thinking in all areas of international law.
Keywords: Law